Towards a smart grid power system in Brazil: challenges and opportunities - Dranka, Geremi Gilson (2020)
The prospects for a smart power system have been widely discussed in the global electricity sector. Decarbonization, Digitalization and Decentralization are considered the main key drivers for this power system transition and Brazil is no exception to this universal trend. A search of the literature revealed few studies which attempt to address the main challenges and opportunities towards a smart grid power system in Brazil. This paper provides an up-to-date assessment of the present and potential capabilities of existing and future technologies, regulations and policies and attempts to identify how these elements are interrelated. Our findings add to a growing body of evidence suggesting that policies for Distributed Generation (DG), Demand-Side Management (DSM) and new tariff schemes are on a path of accelerated deployment in the country. The deployment of storage technologies, however, is at a slow pace of growth. We highlight the need to further develop new business models to address the various decentralized energy technologies and services that are emerging in the sector. The current netmetering system is considered a key issue to be addressed as this regulatory structure may shift the costs from DG to non-DG users.